2008
DOI: 10.1002/ptr.2364
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin‐induced endothelium‐independent relaxation in rat aorta

Abstract: Scutellarin is a flavonoid extracted from the traditional Chinese herb, Erigeron breviscapus Hand Mazz. In the present study, the vasorelaxant effects of scutellarin and the underlying mechanism were investigated in isolated rat aorta. Scutellarin (3, 10, 30, 100 microm) caused a dose-dependent relaxation in both endothelium-intact and endothelium-denuded rat aortic rings precontracted with noradrenaline bitartrate (IC(50) = 7.7 +/- 0.6 microm), but not with potassium chloride. Tetraethylammonium, glibenclamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Interestingly enough, vasorelaxant effects were observed at concentrations that were in the same range as flavonoid plasma levels measured in volunteers after oral ingestion of soy protein drinks [15]. Only recently, Pan et al found that the flavonoid scutellarin dosedependently relaxes both endothelium-intact and endotheliumdenuded rat aortic rings [16]. The authors suggested that inhibition of calcium influx might be involved in the observed vasorelaxant effect.…”
Section: Effects Of Flavonoids On Vascular Calcium Currentmentioning
confidence: 78%
“…Interestingly enough, vasorelaxant effects were observed at concentrations that were in the same range as flavonoid plasma levels measured in volunteers after oral ingestion of soy protein drinks [15]. Only recently, Pan et al found that the flavonoid scutellarin dosedependently relaxes both endothelium-intact and endotheliumdenuded rat aortic rings [16]. The authors suggested that inhibition of calcium influx might be involved in the observed vasorelaxant effect.…”
Section: Effects Of Flavonoids On Vascular Calcium Currentmentioning
confidence: 78%
“…It was identified from a local folk prescription more than 30 years ago and is widely used as a microcirculation promoter for the treatment of cardio-cerebrovascular diseases with a large market share in China. In addition to its vasodilator effect (Pan et al, 2008), other pharmacological activities have been reported for S-7-G, including antioxidant (Hong and Liu, 2004), anti-inflammatory (Luo et al, 2008), and neuroprotective …”
Section: Introductionmentioning
confidence: 99%
“…Scutellarin has been extensively used for the clinical treatment of cardiovascular and cerebrovascular diseases in China for many years. Pharmacological research indicates that scutellarin is associated with antihypertrophic effects [1] , fibrinolysis and anticoagulant effects [2] , protective effects in the brain and heart [3] , hypercholesterolemia suppression [4] , and endothelium-independent relaxation induction [5] . Scutellarin produces an anti-inflammatory effect via actions on arachidonic acid metabolism [6] .…”
Section: Introductionmentioning
confidence: 99%